Contemporary insights into rehabilitation of cervical cancer patients - D. V. Blinov; A. G. Solopova; E. E. Achkasov; D. I. Korabelnikov; S. A. Akavova; V. N. Galkin; Ph. V. Nenakhov; G. K. Bykovshchenko; D. A. Petrenko (Акушерство, гинекология и репродукция, 2023)
Cancer prevalence particularly for cervical cancer (CC) has been steadily increasing tending to rise among young women. Vigorous antitumor treatment approaches employed in CC management have detrimental effects on various aspects of a woman's life. In addition to causing morphofunctional alterations in diverse host organs and systems, such treatment protocols result in psychological and emotional disturbances, sexual dysfunction, and social maladjustment, which collectively profoundly reduce the quality of life (QoL). Integrating timely rehabilitation programs into comprehensive care of such patients can effectively alleviate or minimize complications related to antitumor treatment, improve QoL, and restore a woman's desire for satisfying sexual and social engagement.